2013
DOI: 10.1111/josh.12088
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Professional Development for and Collaboration by Health Education Teachers—41 States, 2000‐2010

Abstract: BACKGROUND Professional development (PD) and collaboration help ensure the quality of school health education. The purpose of this study was to examine trends in the percentage of lead health education teachers (LHETs) receiving PD on health topics and collaborating with other school staff on health education activities. METHODS This study analyzed representative data from 41 states participating in School Health Profiles surveys between 2000 and 2010. Logistic regression examined linear trends in the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Those who teach health education topics are more effective if they have up-to-date knowledge of specific health education topics and the skills needed to engage students (Brener, McManus, Wechsler, & Kann, 2013; Kann, Telljohann, & Wooley, 2007). Teachers can gain this expertise through preservice training (e.g., a degree in health education or certification as a health education specialist) or through professional development (PD; Brener, McManus, Wechsler, & Kann, 2013). PD may increase a teacher’s confidence in teaching, and may provide opportunities for teachers to learn more innovative techniques for engaging students.…”
Section: Introductionmentioning
confidence: 99%
“…Those who teach health education topics are more effective if they have up-to-date knowledge of specific health education topics and the skills needed to engage students (Brener, McManus, Wechsler, & Kann, 2013; Kann, Telljohann, & Wooley, 2007). Teachers can gain this expertise through preservice training (e.g., a degree in health education or certification as a health education specialist) or through professional development (PD; Brener, McManus, Wechsler, & Kann, 2013). PD may increase a teacher’s confidence in teaching, and may provide opportunities for teachers to learn more innovative techniques for engaging students.…”
Section: Introductionmentioning
confidence: 99%
“…Those teachers who had greater interest in the material may have shown greater interest and involvement in the material. Others have documented this phenomenon that a greater interest in the material by the teacher may lead to children having a greater interest in the material (Brener et al, 2013;Lavin, 1993). It also has been documented that teachers with greater job satisfaction (Dinc & Kocyigit, 2017) and greater academic achievement (Uyar et al, 2018) have a greater commitment to teaching.…”
Section: Discussionmentioning
confidence: 98%
“…Research has shown that teachers are more likely to teach a subject if they have a background in the subject. For example, if a person has a physical activity background or instruction on how to incorporate movement into the classroom, they are more likely to teach that subject compared to others (Brener et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Profiles is a surveillance system developed by CDC 17,18 to assess school health policies and practices in states, large urban school districts, and US territories. Profiles surveys are conducted every 2 years by education and health agencies among middle and high‐school principals and lead health education teachers (LHETs).…”
Section: Methodsmentioning
confidence: 99%